Sulci of the liver found after death: Their nature and potential teaching value. Issue 5 (19th March 2012) - Macchi, V.; Porzionato, A.; Stecco, C.; Parenti, A.; Newell, R.L.M.; De, R.
<x xml:space="preserve">Abstract</x> Accessory sulci of the liver are more commonly found after death than in life, raising questions as to their causation and possible classification. We have analyzed a group of 180 livers sampled from un‐embalmed (96) and embalmed cadavers (84). In un‐embalmed cadavers, no accessory sulci were found on the diaphragmatic surface in 58 cases. Diaphragmatic sulci were found in the right lobe of 38 livers. When removed from the abdominal cavity and placed flat on the examination table (the "bench position") all 58 livers without sulci appreciable in the abdominal cavity showed the appearance of two sulci. The first ran from the right side of the inferior vena cava (IVC), curving anteriorly to the inferior border of the liver, at a point midway between the right extremity of the inferior border and the gallbladder fossa, concave towards the left. The second sulcus ran from the left side of the IVC, curving anteriorly to reach the inferior border of the liver at the level of the gallbladder fossa, concave towards the right. With progressive side‐to‐side manual compression, the sulci on the diaphragmatic surface become more evident. Division of the hepatic parenchyma along the two sulci exposed the right and middle hepatic veins respectively in more than 90% of cases. In embalmed cadavers, 24 livers showed antero‐posterior sulci in the superior surface, visible and palpable on the liver examined in situ. When the livers with sulci had been removed from the abdomen for further examination, the appearance of the superior surface did not change. In a removed liver, accessory sulci can be divided into true, "diaphragmatic, " sulci and "false" sulci due to the position of the free liver on the examination table. The "false" sulci may be considered as further morphological evidence of the functional anatomical division of the liver. Their demonstration may also be useful in teaching its topographical and surgical anatomy. Clin. Anat. 26:592–597, 2013. © 2012 Wiley Periodicals, Inc.